The “Auto-sliding Graft” Aortic Wrapping Technique - Estevez-Cid, Francisco; Herrera-Norena, Jose María; de Sierra, Carlos Velasco-García (The Thoracic and Cardiovascular Surgeon, 2019)
We describe the “auto-sliding graft” technique, a different anastomotic option for reconstructive prosthetic procedures on the ascending aorta especially in patients at risk of circulatory arrest with mild aortic dilatation. This simple technique provides not only an important hemostatic reinforcement for the distal aortic graft anastomosis but also a protective effect on the native ascending aorta beyond the suture line.
Keywords: aorta; aortic aneurysm; surgical treatment